Areca catechu nut: a double-edged sword - Sharma, Ajitha (International Journal of Basic & Clinical Pharmacology, 2017)
The chewing of Areca catechu nut, more popularly known as betel nut, is one of the ancient traditions in India and other South-east Asian countries. Other than its role played in religious practices and cultural rituals, areca nut has also been described to have various health benefits, particularly antihelminthic and antiviral properties, in the traditional systems of medicine like Ayurveda. It was observed to produce an antidepressant-like effect by elevating the serotonin and norepinephrine levels in hippocampus of rats. It also exhibited analgesic and anti-inflammatory activities in mice, and displayed in vitro antioxidant activity. Furthermore, it was found to improve spatial memory and learning behaviour in rats.